The spread of COVID-19 false cures in Africa and the contribution of investigative journalism: an example from Ghana - Ribeiro, Pedro Eduardo Oliveira (2020)
Regarding the expansion of the SARS-CoV-2 pandemic, posteriorly named by Coronavirus, the aim for a vaccine for its disease, COVID-19, has been faced as a worldwide challenge. Therefore, either health professionals or not have been trying to conceive alternative cures, including life-threatening ones. This article suggests a content analysis of the report ‘Coronavirus: Ghana 'quack doctors' selling 'cure'’, produced by BBC and conducted by the journalist Anas Aremeyaw Anas. This journalistic work was explored through three thematic categories: traditional media disinformation, interference of the spirituality on the medical practices, and investigative journalism as a way of staving off fake information. The following article debates on how this type of journalism can contribute to fight against media disinformation, generated by beliefs related to the spirituality that currently remains in the African continent and especially in the Ghanaian country, in which the report under analysis focuses on.